Comparison of External Root Resorption in Orthodontic Treatment between Self-Ligating and Conventional Bracket Systems - Bohari, Nuriah; Koah, Noor Airin; Ahmad, Rohana (UI Scholars Hub, 2019)
The relationship between orthodontic bracket systems and external root resorption has remained debatable. Objective: This study compared the magnitude and pattern of the external root resorption of maxillary incisors as induced by self-ligating and conventional bracket systems via cone beam computed tomography and medical imaging programs. Methods: Eight participants were recruited for each bracket system. Their maxillary incisors were scanned at the beginning (T0) and 18 months into treatment (T1). Three-dimensional models of the four maxillary incisors at T0 and T1 were reconstructed using the Mimics program. The difference in root length between T0 and T1 models represented external root resorption. Wilcoxon signed rank and Mann–Whitney tests were conducted to compare resorption within groups and between groups, respectively. The two models were also superimposed in the 3-matic program to reveal the pattern and magnitude of resorption as induced by the different complexities of tooth movement. Results: The root resorption in both groups was significant. The mean root resorption of the conventional system ranged from 0.14 mm to 0.51 mm, whereas the mean root resorption of the self-ligating system varied from 0.16 mm to 0.42 mm, but the mean difference between the groups was not significant. However, the pattern and magnitude of root resorption noticeably differed when the teeth were subjected to different complexities of tooth movement. Conclusion: The magnitude and pattern of root resorption seemed independent of the type of bracket system used but appeared dependent on the complexity of tooth movement.